Preparation, microstructures, and mechanical properties of directionally solidified Al2O3/Lu3Al5O12 eutectic ceramics. Issue 2 (27th October 2021) - Sun, Haofei; Zhou, Cui; Du, Tiefeng; Wu, Zhen; Xian, Quangang; Sun, Luchao; Liu, Jing; Wang, Jingyang
Abstract: Al2 O3 /Lu3 Al5 O12 (LuAG) directionally solidified eutectic (DSE) ceramics with two solidification rates were prepared utilizing optical floating zone (OFZ) technique. The microstructures (eutectic morphology, preferred growth direction and interface orientation) of Al2 O3 /LuAG were characterized, and the mechanical properties (Vickers hardness and fracture toughness) were compared with those of Al2 O3 /REAG (RE = Y, Er, and Yb). Results show that Al2 O3 /LuAG with solidification rate of 30 mm/h has established preferred growth direction in both Al2 O3 and LuAG phases with cellular eutectic structures. While Al2 O3 /LuAG with solidification rate of 10 mm/h only shows preferred growth direction in Al2 O3 phase and presents degenerate irregular eutectic microstructures. Besides, Al2 O3 /LuAG exhibits higher hardness compared with Al2 O3 /REAG (RE = Y, Er, and Yb). In addition, a special attention is focused on the relations among rare earth ionic radius, eutectic microstructures, and mechanical properties of these DSE ceramics. It is demonstrated that a smaller rare earth ionic radius could lead to larger eutectic interspacing as well as higher Vickers hardness of DSE Al2 O3 /REAG, revealing the possibility and feasibility of microstructure control and mechanical properties optimization for DSE Al2 O3 /REAG ceramics by tailoring the rare earth elements.